Simulation and Development of Instrumental Setup to Be Used for Cement Grouting of Sand Soil - Yaser Gamil; Ismail Bakar; Kemas Ahmed (Emerging Science Journal, 2017)
Most of Arab countries areas are occupied with deserts that is covered with sandy soil. Thus, it is necessary to make use of this huge volume of sand to be as construction materials. It is proven that, sand is initially uneven and unstable. It requires pre-modifications of its primer properties in order to be used as construction materials. One of the common techniques is injecting the sand with binders. Many grouting techniques has been implanted to modify or rehabilitate the structure of soil but for sandy soil the methods has not yet been introduced Therefore, this study aimed at developing simulation and instrumental setup to be used for cement grouting. The simulation has been custom made and utilized to form grouted samples for further investigation. The method of injecting sand is by applying pressure to produce force flow in order to be injected into the sand. After the formation of injected sand samples, an experimental investigation was carried out to determine the basic properties. Shear strength of the sand was recorded before and after grouting. It was found that, the shear strength has increased after injecting the sand with cement and the setup has produced accurate grouted samples with even distribution of the cement mix. The results of the various investigations conclusively proved that grouting can be used as an effective way to improve the strength characteristics significantly and can also contribute to the stabilization of sand.